2019
DOI: 10.3390/nu11061241
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Hypothalamic Ghrelin Signaling and Microglia Activation Exacerbate Feeding in Rats’ Offspring Following Maternal Overnutrition

Abstract: Maternal overnutrition during pregnancy leads to metabolic alterations, including obesity, hyperphagia, and inflammation in the offspring. Nutritional priming of central inflammation and its role in ghrelin sensitivity during fed and fasted states have not been analyzed. The current study aims to identify the effect of maternal programming on microglia activation and ghrelin-induced activation of hypothalamic neurons leading to food intake response. We employed a nutritional programming model exposing female W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
4
28
1
Order By: Relevance
“…On this context, recent reports have identified that fetal brain microglia from obese mothers displays a pro-inflammatory cytokine in response to immune LPS challenge (Edlow et al, 2019), a similar pattern of response was identified in glucose-deprived microglial cells, a pathological state included in diabetes (Churchward, Tchir, & Todd, 2018). We also reported that primed microglia from mothers programmed by exposure to western diet display major active profile followed by intrahypothalamic LPS administration (Maldonado-Ruiz, Cárdenas-Tueme, et al, 2019). In fact, microglial depletion still shows a pro-inflammatory and molecular signatures of aged microglia (O'Neil, Witcher, McKim, & Godbout, 2018) and shows hyperactivity after repopulation (Weber et al, 2019), suggesting that primed microglia conserve their original molecular sig- Table 2).…”
Section: Maternal Ob E S It Y Prime S MI Crog Lial Ac Tivati On Andsupporting
confidence: 68%
See 1 more Smart Citation
“…On this context, recent reports have identified that fetal brain microglia from obese mothers displays a pro-inflammatory cytokine in response to immune LPS challenge (Edlow et al, 2019), a similar pattern of response was identified in glucose-deprived microglial cells, a pathological state included in diabetes (Churchward, Tchir, & Todd, 2018). We also reported that primed microglia from mothers programmed by exposure to western diet display major active profile followed by intrahypothalamic LPS administration (Maldonado-Ruiz, Cárdenas-Tueme, et al, 2019). In fact, microglial depletion still shows a pro-inflammatory and molecular signatures of aged microglia (O'Neil, Witcher, McKim, & Godbout, 2018) and shows hyperactivity after repopulation (Weber et al, 2019), suggesting that primed microglia conserve their original molecular sig- Table 2).…”
Section: Maternal Ob E S It Y Prime S MI Crog Lial Ac Tivati On Andsupporting
confidence: 68%
“…Mice exposed to maternal hypercaloric diet during pregnancy have confirmed microglial priming (Banik et al, 2017;Maldonado-Ruiz, Cárdenas-Tueme, et al, 2019) and defective mesocorticolimbic activity to a natural reward and depression-like behaviour in the offspring (Camacho, Montalvo-Martinez, Cardenas-Perez, Fuentes-Mera, & Garza-Ocañas, 2017;de la Garza et al, 2019;Naef et al, 2011).…”
Section: Maternal Ob E S It Y Prime S MI Crog Lial Ac Tivati On Andmentioning
confidence: 87%
“…Bilbo and Tsang previously reported higher density of IBA1 + cells in the hippocampus CA1, CA3, and dentate gyrus of mHFD-exposed male and female rat offspring at adulthood [ 8 ]. Similar effect of IBA1 + increase has also been recently reported in the hypothalamus of rat offspring exposed to a maternal overnutrition model (high-sugar-fat) [ 45 ]. In the present study, we did not observe any change in microglial density in the st rad and st lac mol of the dorsal hippocampus CA1.…”
Section: Discussionsupporting
confidence: 81%
“…Microglial cell density, distribution, gene expression signature, physiological functions, and/or response to immune challenges may be altered upon exposure to various environmental factors, thus impacting on their sculpting of the brain network [ 43 , 44 ]. This phenomenon is referred to as immune priming [ 43 45 ]. Studying microglial priming during sensitive periods like adolescence, in which the brain and especially the hippocampus experience important synaptic changes, may help to understand the pathological cascade underlying mHFD.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, studies in depressed post mortem patients 63 and animal models of chronic stress reported a time-dependent reduction in glial cell number in the CA1 of hippocampus, potentially owing to a selective neuroadaptive response to stress 20 . Also, glial alterations in MDD might presumably be related to active release of S100B by astrocytes 64 or microglia activation during programming 65 . Hippocampal shrinkage may be explained by a decrease in glial cells number and/or loss in the number of neurons due to a neurotoxic effect of glucocorticoids 66 , which are increased in depressed patients 4 , 67 , and have been found in murine models exposed to perinatal high-fat diet 68 .…”
Section: Discussionmentioning
confidence: 99%